Il recycling nel teatro mediale. Gob Squad’s Kitchen dei Gob Squad - Primavesi, Patrick (Kritik. Rivista di letteratura e critica culturale, 2024)
For decades the Gob Squad have been contributing to the development of experimental forms of theater in Germany by bringing back, as Warhol had also done in his own way with Kitchen, the omnipresent devices of medial perception to the elementary situation of theater in when scene of simulation and observation of everyday behavior in a slightly modified frame. This contribution aims to show the construction of their performances through their representations.